DECONSTRUCTING NORMS: AN EXAMINATION OF GENDERED LANGUAGE IN BOY ABUNDA’S WHY CAN’T WE HAVE A GAY PRESIDENT? - Morata, Trixia Kate; Embalzado, Charlyn Mae; Mediado, Francel; Panganoron, Lyndelie; Samantela, Josef Jude; Santiano, Hanna Maria; Villa, Wenalyn; Villaflor, Jannah Veronica; Fajardo, Dan Fereth (Journal of English Education and Linguistics, 2026)
This study examines the speech content of Boy Abunda's Why Can't We Have a Gay President using the Model of Feminist Theory according to Jo Ann Arinder. To investigate traditional gender norms and expectations, the study looks at the language used by Boy Abunda in his speech, "Why Can't We Have a Gay President?" It also aims to identify the gender issues raised in the speech and how feminist theory could help with comprehension. Furthermore, to identify themes and subthemes regarding gender issues and the deconstruction of Boy Abunda, the research study employed a content analysis approach. The results provide insight into how Boy Abunda's presentation of gender issues and language disrupts traditional standards.